Monkeypox and Herpes Simplex Virus Type 2 Coinfection: Case Report of Perianal Lesions in HIV-Positive Patient - Zlámal, Milan; Bartovská, Zofia; Burantová, Anna; Zákoucká, Hana; Jiřincová, Helena; Chmel, Martin; Holub, Michal (Sexually transmitted diseases, 2022)
We report a case of monkeypox and herpes simplex type 2 coinfection in an HIV-positive male patient who has sex with men. This case report describes a diagnostic approach for papular rash in the anal area of the male patient who has sex with men with a history of sexually transmitted disease. This is also the first documented case of monkeypox in the Czech Republic, which was confirmed after a retrospective review of swab samples from a previously hospitalized HIV-positive patient.
Keywords: HIV Infections; koinfekce; HIV infekce; Coinfection; Sexually Transmitted Diseases; Humans; sexuálně přenosné nemoci; lidé; mužské pohlaví; opičí neštovice; Male; lidský herpesvirus 2; herpes simplex; HIV Seropositivity; Mpox, Monkeypox; HIV séropozitivita; Herpesvirus 2, Human; Herpes Simplex